Versailles project on advanced materials and standards (VAMAS) interlaboratory study on measuring the number concentration of colloidal gold nanoparticles. Issue 12 (9th March 2022) - Minelli, Caterina; Wywijas, Magdalena; Bartczak, Dorota; Cuello-Nuñez, Susana; Infante, Heidi Goenaga; Deumer, Jerome; Gollwitzer, Christian; Krumrey, Michael; Murphy, Karen E.; Johnson, Monique E.; Montoro Bustos, Antonio R.; Strenge, Ingo H.; et al.
Abstract : This study compared results of nanoparticle number concentration measurements collected from 74 instruments hosted across 50 laboratories, providing users with useful discussion and reference data to assess and benchmark their measurement capability. Abstract : We describe the outcome of a large international interlaboratory study of the measurement of particle number concentration of colloidal nanoparticles, project 10 of the technical working area 34, "Nanoparticle Populations" of the Versailles Project on Advanced Materials and Standards (VAMAS). A total of 50 laboratories delivered results for the number concentration of 30 nm gold colloidal nanoparticles measured using particle tracking analysis (PTA), single particle inductively coupled plasma mass spectrometry (spICP-MS), ultraviolet-visible (UV-Vis) light spectroscopy, centrifugal liquid sedimentation (CLS) and small angle X-ray scattering (SAXS). The study provides quantitative data to evaluate the repeatability of these methods and their reproducibility in the measurement of number concentration of model nanoparticle systems following a common measurement protocol. We find that the population-averaging methods of SAXS, CLS and UV-Vis have high measurement repeatability and reproducibility, with between-labs variability of 2.6%, 11% and 1.4% respectively. However, results may be significantly biased for reasons including inaccurate material properties whose values are used to compute the number concentration. Particle-counting method results are less reproducibile than population-averaging methods, with measured between-labs variability of 68% and 46% for PTA and spICP-MS respectively. This study provides the stakeholder community with important comparative data to underpin measurement reproducibility and method validation for number concentration of nanoparticles.